The Effect of Village Leadership on Community Participation in Village Development in Village Keramat Gajah - Ella Pradana; Martua Sitorus (Journal of Economics and Business (JECOMBI), 2021)
This study aims to determine the influence of village head leadership on community participation in village development in Keramat Gajah village. Leadership is a set of abilities and personality traits that can influence followers or subordinates to invite or obey their orders with self-awareness to achieve organizational goals. This type of research is quantitative research. The sample used in this study were residents of the Keramat Gajah Village. Number of Samples Using the Slovin formula quoted by Savilla in his book Sadarmayanti and Syarifudin Hidayat, the total sample size is 97 people from a population of 2,978 Kk. The technique used for data collection using a questionnaire (questionnaire). The data analysis technique used is simple linear regression. The results of this study indicate that the independent variable of Village Head Leadership has a positive and significant effect on community participation in Keramat Gajah Village. The contribution of the village head's leadership influence on community participation can be seen from the t value> t table with a calculated value of 2.083> 1.985 and a significant value of 0.000 <0.05.